Avaliação da produção de bioetanol por linhagens de Spathaspora passalidarum isoladas da Floresta Amazônica Brasileira - Monaliza de Araujo Melo (2013)
The production of second generation ethanol from lignocellulosic biomass has been extensively studied as one of the possibilities for obtaining renewable energy. The standardization of effective treatments for recovery and release of high levels of sugar monomers, and the demand for pentoses-fermenting microorganisms capable to tolerate inhibitors present in lignocellulosic hydrolyzates have been the focus of research on the viable economic development of technology for obtaining lignocellulosic ethanol. In this context, the aim of the present work was to study the ability of ethanol production by Spathaspora passalidarum strains, a D-xylose-fermenting yeast species, isolated from rotting wood collected in the Brazilian Amazonian Forest, in different culture conditions (presence and absence of oxygen) and fermentation media, targeting the use of this yeast for the production of second generation ethanol. Furthermore, some characteristics as maximum temperatures for growth and fermentation and ethanol tolerance were determined, which interfere in the physiology of yeast strains. Spathaspora passalidarum strains were able to grow at temperatures between 38°C to 41°C and to ferment D-xylose to ethanol from 34°C to 39°C with a maximum etanol tolerance of 4% (v/v), except for the type strain which tolerated 6% (v/v). Concerning to the fermentation of sugars in the presence of oxygen, etanol yield (Y p/s) and productivity (Qp) ranged from 0.33 to 0.47 g/g and 0.21 to 0.43 g/L.h, respectively. In fermentation under oxygen-limited conditions, Y p/s values ranged from 0.30 to 0.61 g/g and Qp from 0.10 to 0.22 g/L.h. The observed amounts of D-xylose fermentation by-products, such as xylitol and glycerol in both oxygenation conditions evaluated were low, being ethanol the main product formed with concentrations between 9.6 to 18.1 g/L. In a bioreactor fermentation assay under anaerobic condition using soybean hull hydrolyzate without supplementation and detoxification, values of Yps = 0.25g/g and Qp = 0.02 g/L.h were found, with maximum etanol concentration of 3.8 g/L. The results of this study show the biotechnology potential of S. passalidarum strains to obtain lignocellulosic ethanol, in particular for its ability to ferment xylose to ethanol under anaerobic conditions.